CD 1303 - Short stature, high productive potential and industrial quality - Franco,Francisco de Assis (2018)
Abstract CD 1303 is a cultivar indicated for the wheat-producing regions 1, 2 and 3 of the states of Rio Grande do Sul, Santa Catarina and Paraná. It has an early cycle, a short stature and high productive potential (mean of 4311 kg ha-1).